(untitled) (Palíndromo, 2022)
The article presents an analysis of the formation of art teachers in the State of Espírito Santo. It starts from the question about the particularities that constitute the Licentiate Course in Rural Education - Languages, as a multidisciplinary proposal for teacher training. It aims to understand how the multidisciplinary training of the course offered by the Federal University of Espírito Santo is carried out. Data are produced from documentary research, interviews and observation. It bases the analysis on the Marxian-Lukacsian category of particularity. It investigates the changes in art teacher education practices mediated by emerging social demands and legal provisions governing teacher education in Brazil and the implications for the initial teacher education curriculum. Thus, the analysis was developed from the National Curriculum Guidelines for the Undergraduate Course in Visual Arts, and referring to Teacher Training for Basic Education and the legal guidelines for offering a multidisciplinary course for training teachers in the field. This study identifies important changes in the curricula and practices of art teacher education when focused on affirmative policies. The analysis allows us to see important advances in meeting the needs of peasant education, at the same time pointing to the limits of this proposal for initial training.